An Optimization Method for Thrust Allocation of ROV Based on Genetic Algorithm - XU Lei; SONG Junhui; TU Shaoping; ZHU Jun; LI Renxiong (Kongzhi Yu Xinxi Jishu)
To address the problem of output saturation in the thrust allocation of remotely operated vehicles (ROVs), this paper introduces a thrust distribution optimization technique based on genetic algorithm. Initially, a mathematical model describing the horizontal and vertical thrust of an ROV is established, using the spatial configuration of a miniaturized electric ROV's propellers as foundation. Subsequently, genetic algorithm is employed to optimize thrust allocation for the ROV's horizontal and vertical propellers, with results compared to outcomes from a pseudo-inverse method of thrust allocation. Simulation analysis reveals that the thrust allocation optimized via the genetic algorithm can effectively prevent output saturation and ensures that the resultant force or torque from each propeller's output aligns almost exactly with the intended combined force or torque, maintaining an error within ±1%.